2022
DOI: 10.3390/nano12050846
|View full text |Cite
|
Sign up to set email alerts
|

The Performance and Mechanism of a Mg-Al Double-Layer Oxide in Chloride ion Removal from an Aqueous Solution

Abstract: The increasing threat of chloride ions (Cl−) has led researchers to explore efficient removal technologies. Sewage treatment with a double-layer hydroxide/oxide (LDH/LDO) is receiving increasing attention. In this work, Mg-Al LDO adsorbents were produced by the calcination of the Mg-Al LDH precursor, which was constituted by improved coprecipitation. The influence of calcination temperature, calcination time, adsorbent dosage, Cl− initial concentration, contact time, and adsorption temperature on Cl− eliminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…However, only 7.13% and 48.84% of removal efficiency and 6.58 mg/g and 8.65 mg/g of adsorption capacity were obtained with the Mg 2þ /Al 3þ ratios of 2:1 and 4:1 CLDHs. This difference can be attributed to the different interlayer spacing and electrical properties of CLDH caused by varying Mg 2þ /Al 3þ ratios (Xu et al 2022). At a low Mg 2þ /Al 3þ ratio, owing to the ionic radius difference between Mg 2þ (0.65 Å) and Al 3þ (0.50 Å), the excessive Al 3þ may lead to the disorder of CLDH layered structure, which will result in relatively poor adsorption performance (Jiang et al 2021).…”
Section: Comparison Of Mg/fe and Mg/almentioning
confidence: 99%
See 4 more Smart Citations
“…However, only 7.13% and 48.84% of removal efficiency and 6.58 mg/g and 8.65 mg/g of adsorption capacity were obtained with the Mg 2þ /Al 3þ ratios of 2:1 and 4:1 CLDHs. This difference can be attributed to the different interlayer spacing and electrical properties of CLDH caused by varying Mg 2þ /Al 3þ ratios (Xu et al 2022). At a low Mg 2þ /Al 3þ ratio, owing to the ionic radius difference between Mg 2þ (0.65 Å) and Al 3þ (0.50 Å), the excessive Al 3þ may lead to the disorder of CLDH layered structure, which will result in relatively poor adsorption performance (Jiang et al 2021).…”
Section: Comparison Of Mg/fe and Mg/almentioning
confidence: 99%
“…For example, Jiang et al (2021) reported that with the rise in Mg 2þ /Al 3þ ratios from 2 to 5, the interlayer distance increased from 2.82 to 3.16 Å. However, with further increase of Mg 2þ /Al 3þ ratios, the unit charge density became too low, and the electrostatic attraction to anions will decrease consequently (Xu et al 2022). Ogata et al (2018) have reported that the 3:1 Mg/Al CLDH was more effective in removing nitrite and nitrate from water compared with 5:1 Mg/Al CLDH owing to the decrease in electric charge density with varying Mg 2þ /Al 3þ ratio from 3 to 5.…”
Section: Comparison Of Mg/fe and Mg/almentioning
confidence: 99%
See 3 more Smart Citations